Sifat Organoleptik, Sifat Fisik, serta Kadar Β-Karoten dan Α-Tokoferol Emulsi Buah Merah (Pandanus conoideus) - Zita Letviany Sarungallo; Murtiningrum Murtiningrum; Harry Triely Uhi; Mathelda Kurniaty Roreng; Aprida Pongsibidang (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2014)
The objective of this study was to determine the organoleptic and physical properties, and the level of β-carotene and α-tocopherol of red fruit (Pandanus conoideus) emulsion. The emulsion was made by mixing red fruit oil and water in ratio of 7:3, with addition of some emulsifiers as treatments, namely 0.20% of CMC (carboxyl methyl cellulose) (F0), 0.5% of Tween 80 and 0.2% of CMC (F1), and 0.5% of Tween 20 and 0.2% of CMC (F2). Based on the organoleptic evaluation, the most preferred formulation of red fruit emulsion was F1, which have complementary ingredients, namely 0.50% of Tween 80, 0.20% of CMC, 0.06% of sodium benzoate, 0.02% of ethylene diamine tetra acetic acid (EDTA), 1.5% of orange citrus essence, and 15% of sugar. The acceptance scores of the formulation for color, taste, aroma, and texture were 4.5 (like-extremely like), 3.8 (neutral-like), 3.8 (neutral-like), and 4.1 (like), respectively, and the level of viscosity was thick with organoleptic score of 6.1 (thick). Physically, red fruit emulsion has red orange in color, citrus in aroma, sweet in taste, viscous in texture, viscosity 20.5 dPa.s, pH 6.4, and stability 100% in strorage for 30 days at room temperature. The content of β-carotene and α-tocopherol were 14 mg/kg and 229.4 mg/kg respectively.ABSTRAKPenelitian ini bertujuan untuk mengevaluasi sifat organoleptik dan sifat fisik, serta kandungan β-karoten dan α-tokoferol dari emulsi buah merah (Pandanus conoideus). Emulsi buah merah dibuat dengan menggunakan rasio minyak dan air 7:3 dengan perlakuan jenis pengemulsi yaitu F0 (CMC (carboxyl methyl cellulose) 0,20%), F1 (Tween 80 0,5% dan CMC 0,2%), dan F2 (Tween 20 0,5% dan CMC 0,2%). Berdasarkan hasil pengujian organoleptik, formulasi emulsi buah merah yang paling disukai panelis adalah F1 dengan komposisi tween 80 0,50%, CMC 0,20%, sodium benzoat 0,06%, ethylene diamine tetra acetic acid (EDTA) 0,02%, esens orange citrus 1,5%, dan gula 15%, dengan tingkat kesukaan terhadap warna dengan nilai 4,5 (suka sampai sangat suka), rasa 3,8 (netral sampai suka), aroma 3,8 (netral sampai suka), tekstur 4,1 (suka), dan daya alir 6,1 (kental). Emulsi minyak buah merah secara fisik berwarna merah oranye, beraroma orange citrus, berasa manis, bertekstur kental, viskositas 20,5 dPa.s, pH 6,4 dan kestabilan 100% pada penyimpanan 30 hari suhu kamar. Kandungan β-karoten dan α-tokoferol masing-masing sebesar 14 mg/kg dan 229,4 mg/kg.